1986
DOI: 10.1111/j.1398-9995.1986.tb00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Langerhans Cells in Patients with Primary Sjögren's Syndrome

Abstract: IgG-binding to the surface of Langerhans cells (LC) is a feature of primary Sjögren's syndrome and might be associated with qualitative and quantitative defects in LC. Fifteen patients with primary Sjögren's syndrome and 15 healthy controls had a punch biopsy performed from clinically unaffected skin. LC were enumerated in epidermal sheets by an immunoperoxidase technique, as well as demonstrated by immunofluorescence in vertical sections, which were furthermore examined for in vivo deposits of immunoglobulins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…The double-labelling experiments demonstrated that IgG is bound to OKT6-positive LC, but also to a certain degree-to keratinocytes. This is in agreement with a previous study (8), but in the present investigation we stained LC with TRITClabelled antibodies in order to maintain FITC as marker for the IgG staining. It is well-known that epidermal Langerhans cells have surface-bound Fc y-receptors (1 3), but it has recently been reported that keratinocytes also have Fc y-receptors (1).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The double-labelling experiments demonstrated that IgG is bound to OKT6-positive LC, but also to a certain degree-to keratinocytes. This is in agreement with a previous study (8), but in the present investigation we stained LC with TRITClabelled antibodies in order to maintain FITC as marker for the IgG staining. It is well-known that epidermal Langerhans cells have surface-bound Fc y-receptors (1 3), but it has recently been reported that keratinocytes also have Fc y-receptors (1).…”
Section: Discussionsupporting
confidence: 93%
“…The applied monoclonal antibodies against the IgG 1-4 subclasses were chosen because they have been found in a recent IUIS/WHO collaborative study (3) to be reactive and sufficiently specific for an immunohistologic fluorescence technique. We detected deposits of IgG 1 and IgG3 exclusively in the epidermis, in agreement with previous findings (6,8). This, and the observation that the IgG deposits are unrelated to P-IgG levels ( 1 I), indicate a selective binding of IgG to the epidermis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Immunofluorescence showed deposition of IgM and C3, and IgG deposition in the basal and suprabasal layer but not in the dermoepidermal junction zone. 9 The changes seen are thus compatible with NLE and part of the NLS.…”
Section: First Pregnancysupporting
confidence: 54%
“…Various subtypes of DCs found within the inflammatory lesions observed in SS have been reported (83)(84)(85)(86)(87)(88). According to Oxholm et al (89), a characteristic feature of SS is IgG-binding to the surface of lDCs. They further demonstrated a qualitative and quantitative defect in lDCs as measured on epidermal sheets of SS patients.…”
Section: Sjögren's Syndromementioning
confidence: 99%